1997
DOI: 10.1080/00288233.1997.9513247
|View full text |Cite
|
Sign up to set email alerts
|

Microbial degradation of DDT and its residues—A review

Abstract: Microbial degradation of DDT residues is one mechanism for loss of DDT from soil. In this review pathways for biodegradation of DDT, DDD, and DDE by bacteria and fungi are described. Biodegradation of DDT residues can proceed in soil, albeit at a slow rate. To enhance degradation in situ a number of strategies are proposed. They include the addition of DDT-metabolising microbes to contaminated soils and/or the manipulation of environmental conditions to enhance the activity of these microbes. Ligninolytic fung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
140
1
11

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(156 citation statements)
references
References 67 publications
4
140
1
11
Order By: Relevance
“…The high relative abundances of p,p 0 -DDD (20À56%; Figure 4) suggested that DDD was the major degradation product of DDT under anaerobic conditions, similar to the results reported previously. 1,24 Furthermore, p,p 0 -DDE, p,p 0 -DDMU, p,p 0 -DDNU, and p,p 0 -DDNS peaked around 1995 where the relative abundance of p,p 0 -DDT reached the lowest value, corroborating the likelihood for transformation of p,p 0 -DDT into p,p 0 -DDE, p,p 0 -DDMU, p,p 0 -DDNU and p,p 0 -DDNS. On the other hand, the relative abundance of p,p 0 -DDMS did not show such a pattern, probably indicating that it may undergo a different degradation pathway compared to other metabolites.…”
Section: Articlementioning
confidence: 99%
See 1 more Smart Citation
“…The high relative abundances of p,p 0 -DDD (20À56%; Figure 4) suggested that DDD was the major degradation product of DDT under anaerobic conditions, similar to the results reported previously. 1,24 Furthermore, p,p 0 -DDE, p,p 0 -DDMU, p,p 0 -DDNU, and p,p 0 -DDNS peaked around 1995 where the relative abundance of p,p 0 -DDT reached the lowest value, corroborating the likelihood for transformation of p,p 0 -DDT into p,p 0 -DDE, p,p 0 -DDMU, p,p 0 -DDNU and p,p 0 -DDNS. On the other hand, the relative abundance of p,p 0 -DDMS did not show such a pattern, probably indicating that it may undergo a different degradation pathway compared to other metabolites.…”
Section: Articlementioning
confidence: 99%
“…1,4 All these transformations involve reductive dechlorination and have been ratified as the predominant mechanism for DDT transformation under anaerobic conditions. 10 Besides, the present study also favored the degradation pathways of p,p 0 -DDMU to p,p 0 -DDMS and p,p 0 -DDNU to p,p 0 -DDNS through reductive hydrogenation (solid red lines in Figure 3), which have been demonstrated by previous studies.…”
Section: Articlementioning
confidence: 99%
“…This may be attributed to the banned usage of industrial HCHs and DDTs in China for nearly 30 years. However, the half-life of p,p'-DDT in soil is longer than 15 years 28 and DDT together with its metabolites may act as endocrine disruptors, 29 then it is necessary to monitor the status of DDTs in the region continuously.…”
Section: Concentrations Of Ddtsmentioning
confidence: 99%
“…The isomers of this pesticide are released into the environment during manufacture, formulation and usage. "DDT-residues" (DDTr) that collectively represent the different isomers of DDT, DDD, and DDE are now present at numerous sites all around the world [1]. Low solubility, tendency to partition preferentially into 1 lipophilic phase and presence of chlorine atoms make DDTr highly ecotoxic especially to higher organisms [2].…”
Section: Introductionmentioning
confidence: 99%
“…"DDT-residues" (DDTr) that collectively represent the different isomers of DDT, DDD, and DDE are now present at numerous sites all around the world [1]. Low solubility, tendency to partition preferentially into 1 lipophilic phase and presence of chlorine atoms make DDTr highly ecotoxic especially to higher organisms [2]. Major mode of toxicity is the attack on central nervous system, interruption with the functions of respiratory system, DNA damage in blood cells and disruption of synthesis and metabolism of endogenous hormones [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%